Embryotoxic impact of Zika virus in a rhesus macaque in vitro implantation model. Issue 4 (4th January 2020) - Block, Lindsey N; Aliota, Matthew T; Friedrich, Thomas C; Schotzko, Michele L; Mean, Katherine D; Wiepz, Gregory J; Golos, Thaddeus G; Schmidt, Jenna Kropp
Abstract: Zika virus (ZIKV) infection is associated with adverse pregnancy outcomes in humans, and infection in the first trimester can lead to miscarriage and stillbirth. Vertical and sexual transmissions of ZIKV have been demonstrated, yet the impact of infection during the initial stages of pregnancy remains unexplored. Here we defined the impact of ZIKV on early embryonic and placental development with a rhesus macaque model. During in vitro fertilization (IVF), macaque gametes were inoculated with a physiologically relevant dose of 5.48log10 plaque-forming units (PFU) of Zika virus/H.sapiens-tc/PUR/2015/PRVABC59_v3c2. Exposure at fertilization did not alter blastocyst formation rates compared to controls. To determine the impact of ZIKV exposure at implantation, hatched blastocysts were incubated with 3.26log10, 4.26log10, or 5.26log10 PFU, or not exposed to ZIKV, followed by extended embryo culture for 10 days. ZIKV exposure negatively impacted attachment, growth, and survival in comparison to controls, with exposure to 5.26log10 PFU ZIKV resulting in embryonic degeneration by day 2. Embryonic secretion of pregnancy hormones was lower in ZIKV-exposed embryos. Increasing levels of infectious virus were detected in the culture media post-exposure, suggesting that the trophectoderm is susceptible to productive ZIKV infection. These results demonstrate that ZIKV exposure severely impacts the zona-free blastocyst, whereas exposure at the time of fertilization does not hinder blastocyst formation. Overall, early stages of pregnancy may be profoundly sensitive to infection and pregnancy loss, and the negative impact of ZIKV infection on pregnancy outcomes may be underestimated. Abstract : Exposure to Zika virus at the peri-implantation stage of development reduced embryo attachment and altered trophoblast growth, survival, and function in a nonhuman primate in vitro implantation model.